Perverse Disavowal and the Rhetoric of the End - Zupančič, Alenka (Filozofski vestnik, 2023)
The classic formula of disavowal given by Octave Mannoni, “I know well, but all the same,” undergoes interesting and far-reaching permutations in today’s social context. When it comes to dealing with and (not) responding to various crises, we usually point the finger at deniers and their “irrational” attitudes. However, far more common and socially problematic is the attitude that combines full recognition and denial in the same movement. Moreover, knowledge of a problem not only goes seamlessly with ignoring it but seems to make ignoring it possible in the first place. Saying that “we know well” often enables us to ignore the real of that knowledge. Disavowal thus takes a doubly perverse turn, which is the focus of the analysis in this article.